Postcard From Punjab - Nahal, Darashagam (Stimulus: A Medical Humanities Journal, 2023)
These images were captured in my ancestral village in Punjab, India. Golden mustard fields, extensive farm lands, and vibrant sunsets: Punjab's beauty lies in its rural simplicity.